Evolutionary development and co‐phylogeny of primate‐associated bifidobacteria. (24th June 2020) - Lugli, Gabriele Andrea; Alessandri, Giulia; Milani, Christian; Mancabelli, Leonardo; Ruiz, Lorena; Fontana, Federico; Borragán, Santiago; González, Andrea; Turroni, Francesca; Ossiprandi, Maria Cristina; Margolles, Abelardo; van Sinderen, Douwe; et al.
Summary: In recent years, bifidobacterial populations in the gut of various monkey species have been assessed in several ecological surveys, unveiling a diverse, yet unexplored ecosystem harbouring novel species. In the current study, we investigated the species distribution of bifidobacteria present in 23 different species of primates, including human samples, by means of 16S rRNA microbial profiling and internal transcribed spacer bifidobacterial profiling. Based on the observed bifidobacterial‐host co‐phylogeny, we found a statistically significant correlation between the Hominidae family and particular bifidobacterial species isolated from humans, indicating phylosymbiosis between these lineages. Furthermore, phylogenetic and glycobiome analyses, based on 40 bifidobacterial species isolated from primates, revealed that members of the Bifidobacterium tissieri phylogenetic group, which are typical gut inhabitants of members of the Cebidae family, descend from an ancient ancestor with respect to other bifidobacterial taxa isolated from primates.